Analisis Kritis Etika Politik Kasih Tinjauan Fratelli Tutti 154 Perang Melawan Politik Individualisme - Aliano, Yohanes Alfrid; Welan, Yeremia Anton Julianus; Lau, Stefanus; Arianto, Josep (Kamaya: Jurnal Ilmu Agama, 2023)
This study discusses the phenomenon of the "Politics of Love" as a response to the increasing politics of individualism in the context of critical analysis of Political Ethics, with reference to the views expressed in Fratelli Tutti's encyclical 154. The background of this research involves concerns about globalization which increasingly emphasizes individualism in dynamics. Politics, which can threaten the principles of social solidarity and bonum commune. The main objective of this research is to identify the key elements of the concept of "Politics of Love" advocated by Fratelli Tutti as an alternative to the politics of individualism. The method used involves critical text analysis of the 154 encyclicals, with a focus on historical context and in-depth theological interpretation. The results of this study reveal that the "Politics of Love" advocates the adoption of a more inclusive, collaborative, and caring approach to the common good. This includes rejecting narrow views that only prioritize the interests of certain individuals or groups. This research also highlights the importance of moral leadership in promoting solidarity, shared prosperity, and the spread of human values. This research shows that in facing the political challenges of increasingly strong individualism, the concept of "Politics of love" can be an ethical guide that has the potential to restore the principles of inclusiveness and mutual care in the world of politics. By referring to the teachings of Fratelli Tutti, this research underscores the need for a transformation in the political paradigm towards an approach that is more oriented towards love, equality and social justice for the common good.